2020
DOI: 10.24221/jeap.5.1.2020.2675.088-097
|View full text |Cite
|
Sign up to set email alerts
|

Land-use and coverage in the structure of the landscape in a Tropical Dry Forest in northeast Brazil

Abstract: Landscape Ecology using GIS is applied to understand the effects of forest fragmentation and makes it feasible mainly for extensive areas, through the possibility of analyzing both the variety of units that compose it in time. This study aims to analyze the land use and coverage of tropical dry forests and to characterize their landscape structure in an area of the municipality of Floresta, Pernambuco, Brazil, in order to understand how the landscape configuration can influence the conservation. Orbital images… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…Caatinga showed the potential for high alteration, largely in in well preserved areas. In a study on Pernambuco-Brazil that analyzed Land Remote-Sensing Satellite imagery, Dos Santos et al 31 found that fragments of dense vegetation were more exposed to degradation and consequent landscape alteration, potentially increasing the burning and resultant carbon emissions in Caatinga. It is worth noting that Caatinga is the most populated biome and occurs in a drier region of Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caatinga showed the potential for high alteration, largely in in well preserved areas. In a study on Pernambuco-Brazil that analyzed Land Remote-Sensing Satellite imagery, Dos Santos et al 31 found that fragments of dense vegetation were more exposed to degradation and consequent landscape alteration, potentially increasing the burning and resultant carbon emissions in Caatinga. It is worth noting that Caatinga is the most populated biome and occurs in a drier region of Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that Caatinga is the most populated biome and occurs in a drier region of Brazil. As such, in addition to landscape changes as a result of increased fires, the acceleration of fires from climate change may lead to dramatic social consequences 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Os autores utilizaram dados Landsat (TM, ETM+ e OLI) em um intervalo de 31 anos (1985-2015) e compararam os índices espectrais Enhanced Vegetation Index (EVI), Normalized Difference Vegetation Index (NDVI) e albedo de superfície, tendo o último apresentado a melhor acurácia. Em uma área de Pernambuco, Santos et al (2020) classificaram o uso e cobertura da terra utilizando a técnica de máxima verossimilhança em dados Landsat de 2007 e 2017. Por fim, Silveira et al 2018combinaram pela primeira vez a classificação das fitofisionomias da Caatinga com atributos físico-químicos do solo usando dados do Sentinel-2 e LiDAR.…”
Section: Análise Bibliográfica: a Vegetação Da Caatinga Na Literaturaunclassified